Journeys to functionality: A dimensional analysis of personal narratives of recovery from depression - Settrisman R.; Mishra A.K. (My University, 2025)
Background: Recovery from depression constitutes a long journey that is understood as a unique and multifaceted process encompassing various dimensions. To understand what constitutes recovery from depression and to develop greater insights into the unique dimensions of the recovery journey, the study of recovery memoirs is essential. Method: This article performs a dimensional analysis on six Indian first-hand accounts of recovery from depression collected in Amrita Tripathi and Arpita Anand's Real Stories of Dealing with Depression to examine the journeys toward healing and the uniqueness of the recovery processes. Through the dimensional analysis, four core dimensions of recovery from depression—Problems, Social Supports, Position of Recovery and Functionality—are identified. The process of recovery, consisting of understanding the problems (causes) through sensed adversities (sensed effects), making use of received social supports to transform oneself, finding out the position of recovery, and lastly, functioning peacefully for living, corresponds to the four dimensions of recovery. Drawing on Herbert Blumer's theory of social interactionism, the article examines how different individuals interpret their experiences of depression in unique ways and develop distinctive recovery strategies. Discussion: The identified dimensions of recovery correspond to the need for unique approaches to recovery articulated by each of the narrators. The selected narratives reveal that the problems are unique, and for each of the unique problems, there has to be a distinctive support mechanism. The recovery narratives are centred around the unique problems wherein the individuals attempt to understand what happened to them and why it happened. Conclusion: The article concludes by suggesting that healthcare practitioners can utilise the dimensions and the subdimensions as a lead to understand fully how their clients conceptualise their problems and try to understand how each client defines the recovery itself. © 2024 John Wiley & Sons Ltd.